Effect of percutaneous transthoracic lung biopsy on oxidative metabolism in sheep - Silva, Andreza A. [UNESP]; Ferreira, Danilo O.L. [UNESP]; Santarosa, Bianca P. [UNESP]; Dias, Adriano [UNESP]; Damasceno, Débora C. [UNESP]; Gonçalves, Roberto C. [UNESP] (Medpharm Publications, 2012)
This study aimed to assess the effect of percutaneous transthoracic lung biopsy on the oxidative metabolism of sheep by measuring the oxidative stress markers of superoxide dismutase (SOD), total glutathione (GSH-t), peroxidase (GSH-Px) and thiobarbituric acid reactive substances (TBARS) in the red cells of these animals. Blood samples were collected from 20 clinically healthy sheep prior to, and 30 min after, percutaneous transthoracic lung biopsy. After biopsy, there was a significant decrease (p < 0.05) in SOD and GSH-Px activity, with no significant change (p ≥ 0.05) in GSH-t and TBARS concentrations. These results showed that percutaneous transthoracic lung biopsy did not significantly affect the oxidative metabolism of sheep 30 min after the procedure, which may be used widely in this species without causing serious tissue damage. © 2012. The Authors.
Keywords: glutathione; peroxidase; superoxide dismutase; thiobarbituric acid reactive substance; aerobic metabolism; animal experiment; animal tissue; blood analysis; concentration (parameters); enzyme activity; erythrocyte; female; lung biopsy; male; nonhuman; oxidative stress; percutaneous transthoracic lung biopsy; sheep; tissue injury; Animalia; Ovis aries